When Airbnb Sits in the Control Room: Platform Urbanism as Actually Existing Smart Urbanism in Reykjavík - Söderström, Ola; Mermet, Anne-Cécile (Frontiers in Sustainable Cities, 2020)
Platform urbanism understood as the impact of digital platforms on the materiality, daily lives and governance of cities is, we argue in this paper, a powerful form of actually existing smart urbanism. While public attention tends to be grabbed by the control rooms and sensors of smart city narratives, the increasing density of interactions with, and transactions through, digital platforms rapidly and profoundly reshapes the dynamics of cities and their regulation. The paper investigates platform urbanism by focusing on the ‘Airbnb effect’ in the city of Reykjavik. Based on this case-study we argue that through their ubiquity and the control they have over code and data, platform companies increasingly tend to sit in cities’ control rooms. In its conclusion, the paper calls for more studies on three issues – ‘datapower’; platform effects on cities; and regulatory frames – to nurture a democratic debate on this ongoing corporatization of urban governance.